Descriptive analysis of spatial distribution and service provision of hookah in establishments in Puducherry, a Union Territory of South India - Paulraj, Deepthi; Narayanan P. P., Sreeshma; Kumar R., Suriya; Ulaganeethi, Revathi; Gola, Anurag; Kar, Sitanshu Sekhar (International Journal Of Community Medicine And Public Health, 2025)
Background: The usage of novel and emerging tobacco products is increasing among tobacco users, including adolescents and adults. Hence, we aimed to investigate the density of hookah bars and the provision of hookah services in the union territory of South India. Methods: A cross-sectional study was conducted during May 2024 using online searches, field visits, and resident consultations, focused on tourist spots and college areas, to identify the establishments with hookah availability. A semi-structured questionnaire was used to collect data, including the type of facility (bar, restaurant with bar, or pub), area/street name, presence of hookah services (yes/no), and location through a geotagging app. Prevalence of hookah bars providing services was reported as a proportion with a 95% confidence interval, and geotagging was performed to analyze density patterns. Results: Among the 290 facilities assessed, a significant concentration of hookah establishments was observed around White Town Beach, a major tourist hotspot. Of these, 151 facilities were accessible, and 51 confirmed offering hookah services, resulting in a prevalence of 33.8% (95% CI: 26.7% - 41.6%). The analysis further revealed that hookah establishments were clustered in urban areas, and their presence was relatively sparse in peripheral regions. Conclusions: Nearly one-third of facilities offering hookah services are clustered around tourist spots in urban areas. The findings highlight the need for targeted public health interventions and stricter regulatory measures. Further research is required to explore the determinants of hookah availability and usage trends, particularly among youth, to inform effective policy development.